Critical reduction of the geographic distribution of Cyanocyclas (Cyrenidae: Bivalvia) in Uruguay. Issue 5 (2nd August 2018) - Clavijo, Cristhian; Carranza, Alvar
Abstract: The South American endemic corbiculid genus Cyanocyclas comprises about 15 nominal species described from Uruguay. Of these, only two are at present considered valid species. Several authors have reported population declines of these species after the settlement and spread of the invasive genus Corbicula, and even the disappearance of Cyanocyclas populations from certain localities. This article reviews the historical and present geographical distribution of Cyanocyclas spp. in Uruguay. Of the localities where Cyanocyclas spp. have been reported previously, 75% were re‐surveyed during 2009 and 2012, but Cyanocyclas spp. were found to be present in only five of these locations (7.1%). In addition to Cyanocyclas limosa and Cyanocyclas paranensis, at least three morphotypes not attributable to any of these species were found; therefore, the reduction in range may be more severe than expected. The putative effect of the invasive bivalve Corbicula fluminea and other stressors is briefly discussed. The adequate management of the few extant populations is a key issue in ensuring the conservation of Cyanocyclas .